Manganese oxide-based catalysts for low-temperature selective catalytic reduction of NOx with NH3: A review - Liu, Chang; Shi, Jian-Wen; Gao, Chen; Niu, Chunming (Applied catalysis. A, General, 2016)
[Display omitted] •Recent progress on Mn-based catalysts for low temperature SCR de-NOx was reviewed.•Special attention was paid to clarify the various roles played by each component.•The effects of supports were emphasized according to the type of supports.•Reaction mechanism and future direction for SCR catalysts were discussed. Selective catalytic reduction (SCR) technology has been widely used for the removal of NOx from flue gas. However, it is still a challenge to develop novel low-temperature catalysts for SCR of NOx, especially at temperatures below 200°C. This paper reviewed the recent progress on the Mn-based catalysts for low-temperature SCR de-NOx with NH3. Catalysts were divided into four categories, single MnOx, Mn-based multi-metal oxide, Mn-based multi-metal oxide with support, and Mn-based monolith catalyst. In the section of single MnOx, the effects of several factors, such as Mn oxidation state, crystallization state, specific surface area and morphology on catalytic activity were systematically reviewed. In the section of multi-metal oxide catalysts, the various roles played by the components of catalysts were intentionally summarized from four aspects, improving de-NOx efficiency, enhancing N2 selectivity, improving resistance to SO2 and H2O, extending operation temperature window, respectively. Moreover, the newly emerging morphology-dependent nanocatalysts were highlighted at the end of this section. In the introduction of supported metal oxide catalysts, the effects of supports were systematically analyzed according to their types, such as Al2O3, TiO2, carbon materials, etc. Considering the actual operation, Mn-based monolith catalysts were also introduced with regard to monolith supports, such as ceramics, metal wire mesh, etc. Subsequently, NH3-SCR mechanisms at low temperature, including E-R and L-H mechanisms, were discussed. At last, the perspective and the future direction of low-temperature SCR of NOx were proposed.